The Car Sharing Economy: Interaction of Business Model Choice and Product Line Design - Bellos, Ioannis; Ferguson, Mark; Toktay, L. Beril (Manufacturing and Service Operations Management, 2017)
Several auto manufacturers have recently introduced car sharing programs. Although the structure of most programs is the same, there is no clear dominant strategy for the type of vehicles that should be provided through car sharing. In this paper, we consider an original equipment manufacturer (OEM) that contemplates car sharing and designs its product line by accounting for the trade-off between driving performance and fuel efficiency under CAFE standards. Customers have different valuations of driving performance and decide whether to buy, join car sharing or rely on their outside options. We find that the OEM increases the fuel efficiency of the vehicles it provides through car sharing. This higher efficiency enables the OEM to charge a higher selling price to the higher end of the market, thus increasing its profit. This is especially beneficial to higher-end OEMs that face greater cannibalization and can explain why Daimler and BMW have been particularly active in introducing car sharing. Offering car sharing is not always environmentally beneficial. Even when it is, we find that doing so may reduce the OEM’s Corporate Average Fuel Economy (CAFE) level. In such cases, incentive multipliers should be granted for each shared car. Finally, if anticipating aggressive CAFE standards, OEMs may introduce car sharing to better absorb the increase in the production cost. The online appendix is available at https://doi.org/10.1287/msom.2016.0605 .